Cytotoxicity and Exposure Assessment of PM2.5 in a Residential Home during COVID-19 Lockdown - Ummi Sabariah Mahamud; Armania Nurdin; Eliani Ezani (Aerosol and Air Quality Research)
Abstract As individuals become more confined to their homes, especially during the COVID-19 lockdown and the post-pandemic era, human activities will continue to generate more indoor particles. However, the toxicity effects of indoor particles remain unknown during residents’ occupancy time. Eighteen 24 hours of indoor and outdoor PM2.5 samples were collected using 37 mm polyvinyl chloride (PVC) filter within a residential terrace house in Serdang, Selangor, during the 2021 Malaysia lockdown between February and March 2021. PM2.5 samples were then extracted using methanol. MTT assay determined the cytotoxic activity of extracted indoor and outdoor PM2.5 treated at different concentrations (25–200 µg mL−1) on human lung cells (MRC-5) at a 24-hour incubation period. The 24-h mass concentration of outdoor PM2.5 (41.4 ± 1.99 µg m−3) was significantly three times higher than indoor PM2.5 (11.8 ± 0.60 µg m−3) (p < 0.05). However, exposure to indoor PM2.5 at higher concentrations (100 and 200 µg mL−1) on lung cells (MRC-5) significantly reduces cell viability compared to outdoor PM2.5, suggesting that exposure to indoor PM2.5 causes toxicity to the lung cells compared to outdoor PM2.5. In parallel, indoor real-time PM2.5 measurements were recorded in the kitchen during cooking and non-cooking days. We found cooking days generated higher indoor PM2.5 concentrations (maximum PM2.5 = 75.0 µg m−3), suggesting that cooking activity might contribute to the toxicity of indoor PM2.5. Due to the limited yield of indoor and outdoor PM2.5, further optimization on the extraction of PM2.5 should be carried out to evaluate further the mechanism of cytotoxicity of indoor PM2.5 on the lung cells.